How the Garcia girls lost their accents - Alvarez, Julia (Algonquin Books of Chapel Hill, 2010)
In the 1960s, political tension forces the García family away from Santo Domingo and towards the Bronx. The sisters all hit their strides in America, adapting and thriving despite cultural differences, language barriers, and prejudice. But Mami and Papi are more traditional, and they have far more difficulty adjusting to their new country. Making matters worse, the girls--frequently embarrassed by their parents--find ways to rebel against them.